Effects of CPAP treatment on cardiac structure and function in individuals with obstructive sleep apnea and cardiovascular disease: a prospective 6-month randomised control trial. (25th November 2020) - Franke, K; Loffler, K.A; Nicholls, S.J; Anderson, C.S; Cowan, B.R; McEvoy, R.D; Young, A.A; Verjans, J.W
Abstract: Background: Obstructive sleep apnea (OSA) is associated with an increased risk of cardiovascular events. The influence of continuous positive airway pressure (CPAP) on cardiac function remains uncertain. Purpose: To prospectively determine the effects of CPAP on cardiovascular function, as measured by cardiac magnetic resonance imaging (CMR) as a sub-study of the international SAVE trial (NCT00738179). Methods: Participants with OSA and established cardiovascular disease were randomized to CPAP treatment plus usual cardiovascular care or Usual Care alone. Primary outcomes were defined as change in ventricular ejection fraction (EF) and stroke volume (SV) between baseline and 6-month follow-up both groups. Secondary outcomes included other ventricular parameters including volumes, mass, and strain, and atrial parameters. Results: 140 participants were included; mean CPAP adherence in those allocated to receive the treatment was 4.31±2.45 hours per night. Most were male (91%) and had moderate-severe OSA with minimal daytime sleepiness. There were no significant differences in left or right ventricular EF between groups after 6 months of treatment. There was an 8.5 mL increase in LV SV (95% CI; [4.3–12.6], p<0.001) and a 7.7 mL increase in RV SV (95% CI; [3.4–12.0], p<0.001) in the CPAP group compared to Usual Care. CPAP also affected left and right ventricular EDV, RV strain, and atrial parameters. Conclusions: In the first prospective CMR imaging study of patients with OSA and cardiovascular disease, CPAP treatment did not change EF after 6 months, but did have significant effects on other parameters of cardiac function. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Respironics Foundation; Australian National Health and Medical Research; New Zealand Health Research Council